Candida glabrata gene expression response upon engulfment by THP-1 macrophages - Ismail, Elysha Nur; Than, Leslie Thian Lung (2024)
Candida glabeuta has emerged as a significant pathogen, particularly in immunocompromised individuals. It exhibits a unique capability to persist within macrophages, thereby prolonging the infection. This study investigates the alteration of ICLI and MNN2 gene expression in engulfed C glabrata during macrophage interaction to understand its adaptive strategies against the host immune system, specifically focusing on genes linked to altered metabolism and cell wall modifications. The rise in multidrug-resistant C. globroto strains limits treatment options, necessitating a congrefensive understanding of its gone functions and interactions.